Acne relapses: impact on quality of life and productivity. (22nd February 2019) - Dreno, B.; Bordet, C.; Seite, S.; Taieb, C.; ,
Abstract: Background: Acne is a common skin disease that mostly affects teenagers, with a negative impact on quality of life. Recently, adult acne and acne relapses have increased in frequency, for yet unknown reasons. Objective: This non‐interventional, real‐life study sought to investigate the rate of acne relapses and their impact on quality of life and productivity (loss/absenteeism) among teenagers and adults. Methods: An online self‐administered questionnaire was proposed to ≥15‐year‐olds suffering from acne who spontaneously consulted their dermatologist. To ensure homogeneous assessment of acne severity, the global acne severity scale was applied. Quality of life was assessed via Cardiff Acne Disability Index (CADI), SF12‐physical score and SF12‐mental score questionnaires. Productivity loss or absenteeism in middle/high school was estimated based on the number of days off work or school over the last 30 days. Results: Overall, 1048 questionnaires were considered assessable, with 448 (43%) mild acne, 434 (41%) moderate acne and 166 (16%) severe acne. Overall, 755 (72%) participants were in middle/high school, 267 (25%) employed and 26 (3%) with no professional activity. Considering the population by age groups, 68% ( n = 716) were ≤20‐year‐olds and 32% ( n = 332) >20‐year‐olds, with a mean age of 20.26 (SD: 7.43) years. Acne relapses were reported by 44% of respondents. Analyses revealed that poorer quality of life scores was observed in acne relapsers vs. non‐relapsers, with a significant difference for CADI scores ( P < 0.01) in >20‐year‐olds. Acne‐related absenteeism was recorded in 5.7% of cases. On multivariate analyses, after adjusting for other variables, acne relapse was proven a significant determinant of absenteeism/productivity loss. Conclusion: This real‐life study first demonstrated acne relapse rates of 44%, which appeared to be generation‐dependent, affecting 39.9% of ≤20‐year‐olds vs. 53.3% of >20‐year‐olds. Acne relapses were significantly associated with impaired quality of life and productivity loss/absenteeism.